Antimicrobial activity of ethanolic extraction of zingiber zerumbet rhizome against skin microorganisms / Dzarana Mat Safri - Mat Safri, Dzarana (2015)
Zingiber zerumbet is a perennial plant that can be found in many tropical countries. Its main part is rhizome which widely used as traditional medicine for long time. The rhizome is able to cure inflammation, sore throat, diabetes, swelling chest pain, bronchitis and many more. Moreover, it is also reported to have antimicrobial activity. There are lots of antimicrobial soaps available in markets nowadays which contain an active ingredient or antimicrobial agent, triclosan. Triclosan has been reported to affect the health of user and environment especially for the long term usage. In order to make sure that antimicrobial soaps are healthy to use, triclosan need to be changed with natural products. Hence, this study was done to determine the antimicrobial activity of Zingiber zerumbet rhizome against skin microorganisms as well as to detect its bioactive compounds. The Zingiber zerumbet rhizome was extracted with ethanol then performed antibacterial susceptibility testing (AST) against tested microorganisms using disc diffusion method. Then, Minimum Inhibitory Concentration (MIC) was done using broth microdilution method with microtiter plate. Shower gel was prepared from Zingiber zerumbet rhizome extract to test against the tested microorganisms using disc diffusion method. The preliminary phytochemical screening was done using different types of reagent for different bioactive compounds. The result for AST show that most sensitive with the largest diameter of inhibition zone, 11 mm. It was followed by Candida albicans (10.33 mm), Proteus mirabilis (8 mm) and then Staphylococcus aureus (7.67 mm). Both Pseudomonas aeruginosa and Acinetobacter baumannii showed no inhibition zone. The MIC showed that Proteus mirabilis had the lowest MIC value (15.63 mg/ml). Staphylococcus aureus had 31.25 mg/ml meanwhile both Staphylococcus epidermidis and Candida albicans had the same value, 62.5 mg/ml. When tested with Zingiber zerumbet shower gel, none of the tested microorganisms were sensitive except for Staphylococcus epidermidis (11.67 mm). The preliminary phytochemical screening revealed that Zingiber zerumbet rhizome contains alkaloids, flavonoids, proteins and amino acids and triterpenoids. This finding showed that Zingiber zerumbet rhizome extract had antimicrobial activity against skin microorganisms and had a potential to use as natural product in antimicrobial soaps replacing the triclosan